Religious Identities and the Global South: Porous Borders and Novel Paths - Wilfred, Felix (New Approaches to Religion and Power, 2021)
1. Introduction -- 2. Religion: A Question of Identity -- 3. Religious Identities: From the Colonial to the Global -- 4. Conflicting Religious Identities: The Political Turn -- 5. Religious Fundamentalism in the Age of Globalization -- 6. Novel Ways of Being Religious -- 7. Globalization and New Religious Movements -- 8. Religions in Diaspora: The Case of South Asian Migrants -- 9. Religious Freedom: Beyond the Liberal Paradigm -- 10. Religious Identities by Choice and the Politics of Conversion -- 11. Changing Ethical Discourses and Religious Identities -- 12. Religion and Public Life: Continuing Debate -- 13. From Porous Borders to Cosmopolitan Horizons: Beyond Interreligious Dialogue and Multiple Belonging -- 14. By Way of Conclusion: The Present Crisis and the Religions of the Future.